"I Stay by Myself": Social Support, Distrust, and Selective Solidarity Among the Urban Poor1. Issue 4 (22nd July 2016) - Raudenbush, Danielle
Abstract : Significant debate exists about whether the black urban poor rely on each other for support. Currently, two perspectives dominate: the pervasive solidarity perspective, which asserts that support is widespread in poor, black communities, and the distrust‐individualism perspective, which claims that, in these communities, pervasive distrust undermines social cohesion and people use individualistic strategies for solving problems. Based on fieldwork in an African American public housing development, I present the concept of selective solidarity, which suggests that social life in these communities is neither as cohesive nor as individualistic as what past perspectives suggest. With selective solidarity, people rely on one another for support but selectively choose exchange partners, restricting exchange networks. Selective solidarity helps us understand how people manage sentiments of distrust while developing strategies for coping with material deprivation. Findings also have implications for the study of urban poverty. While my informants frequently stated that they "stay by themselves, " which implies individualism, they actually have meaningful exchange relationships. I argue that this contradiction suggests that they have multiple frames for approaching social life. We must consider such frames to avoid drawing misinformed conclusions, such as that the urban poor do not have supportive relationship when in fact they do.